Potensi Lactobacillus acidophilus dan Lactobacillus fermentum dari Saluran Pencernaan Ayam Buras Asal Lahan Gambut sebagai Sumber Probiotik - Manin, Fahmida (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
Probiotics are cultures of microorganisms included in the diets of cattle through mixing to ensure the  availability  of  a  population  of  organisms  in  the  gut.  The  culture  contains  a  specific  bacterium, resistant in dry situations. Probiotics may contain one or more strains of microorganisms in the form of powder, tablets, granules or paste and can be given to livestock is directly through the mouth or mixed with water and feed. Probiotic products in general form of Lactic Acid Bacteria (LAB), and some of the genus Bacillus,  but not  all  types  of Lactic Acid Bacteria  and Bacillus  included  in  probiotic  bacteria. Lactobacillus  casei  and  Lactobacillus  acidophilus  reported  to  act  as  probiotics  and  to  increase  body weight  in  chickens.  Similarly,  Bacillus  circulans  and  Bacillus  Sp  isolated  from  the  digestive  tract Kerinci local ducks can be used as a source of probiotics on chickens and ducks and effective for use as a substitute  for  antibiotics. This  study  aimed  to determine  the  type  and distribution of the  dominant  microbes  in  each  segment  of  the  digestive  tract  of  chickens  reared  in  peatlands,  through  isolation technique,  identification  and  selection,  and  testing  probiotic  properties,  including  resistance  to  acid, resistance  to  bile  salts  and  koagregasi  test  between  microbes.  Results  Identification  of  the  chicken digestive  tract  bacteria  dipe;  ihara  in  peatlands  obtained  Lactobacillus  acidophilus  and  Lactobacillus fermentum. The test results obtained on the nature of the two types of probiotic bacteria were resistant to a pH ranging  from pH 2.0 to pH 4, for 14 hours of incubation, that was resistant to bile salts up to 14 hours of incubation and hade a positive coaguration. In conclusion, probiotics production is expected to be applied to poultry, especially chickens.